Come promuovere la cultura dell’etica e della legalità per uno sviluppo sostenibile delle comunità - Concettina Titty Siciliano (Labour & Law Issues, 2015)
The article develops with a multidisciplinary approach the theme of the policies of contrast, prevention and repression of “corruption”, the latter understood as a factor of socio-anthropological degradation that threatens the well-being of individuals in the communities in which they live, work and interact. According to the context analysis of an attentive monitoring carried out by the European Union, corruption is a “systemic” phenomenon, opposition to which calls for more effective political commitment as it “seriously harms the economy and society as a whole”.A serious and effective policy of opposition to the corruptive phenomenon identifies itself by at least two dynamic and interacting aspects: for the capacity of vision and interaction of a general, planning and systemic type between different levels, and for the ability of (penetration) action in the context, correction and punishment, according to a short, medium and long-term perspective. The effectiveness and success of a serious (public) action of opposition to corruption, therefore, depends on the willingness to respond to a pervasive phenomenon with appropriateness of investigation, knowledge, method and instruments that allows actions to be planned and arranged and differentiating them over a sufficient time-period, because of the concrete risk found in the various sectors and levels of Government. That is, instruments are needed that strengthen the capacity of control and of ethical enhancement of the human capital of organisations for the areas of intervention, having an influence on the inherent risk of corruption in each social-political-organisational system.Prevention through the culture of ethics and legality takes on a crucial role together with the training and orientation of the human capital towards positive values of integrity, of the selection of merit and the guarantee of equal opportunities. Prevention policies that promote the culture and dissemination of ethics, the rule of law and of anti-corruption in relations between private individuals and public authorities, as well as generally in custom and lifestyle, are practical for the objective of a serious opposition to the corruption and dishonesty - and hence the inefficiency - of public institutions.